Pengembangan Media Pembelajaran Android pada Materi Dampak Sosial Informatika Kelas X SMA Negeri 1 Anjongan - Atiqah, Saziyah; Dharmayanti, Winna; Nurcahyo, Ratih Widya (Universitas Lampung, 2025)
This study aims to develop and evaluate Android-based learning media on the subject of the Social Impact of Information Technology for 10th grade students at SMA Negeri 1 Anjongan. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of this study consist of three validators: one design expert, two media experts, and one subject matter expert, as well as 35 students involved in two testing phases (five students in the small-scale pilot test and 30 students in the large-scale pilot test). The media was developed using MIT App Inventor, featuring subject matter content, instructional videos, and interactive practice questions. The validation results showed that the media received a feasibility score of 88% from the design expert, 91% from the media expert, and 90% from the content expert, categorized as “highly feasible.” Meanwhile, the student trial showed that 93% of students responded positively to the learning media, with increased student engagement and understanding of the material. The media was also deemed practical and flexible as it could be accessed independently via Android devices outside of school hours. Based on these results, the developed learning media was proven to be feasible and effective for use in teaching the Social Impact of Informatics subject at the high school level.Keywords: Android, Informatika, Media Pembelajaran, MIT App Inventor, Motivasi Belajar